Mapping Bulgaria's Future : Inclusive Growth and Productive Jobs - World Bank (Washington, DC, 2014)
The newly elected government takes office at a time of stark economic challenges. The outfall of the global economic crisis threatens to undo many of the achievements of the recent past, derail convergence with the European Union (EU), and heighten social vulnerability. The election of a strong government offers a timely opportunity to restore and broaden the economic reform agenda which had been initiated before EU accession and but lost some momentum since 2007. Decisive action could shorten the length and reduce the depth of the crisis by restoring market confidence and improving economic prospects. Restoring the health of the economy and returning to the convergence path requires concerted policy actions to unwind economic imbalances and advance much needed structural reforms. The two-way policy response would aim to: 1) bring about fiscal consolidation and restructure public finances, strengthen financial stability, and mitigate the social impact of the crisis in the short-run; 2) and step up structural reform to address deep seated economic problems which both magnify the impact of the international crisis and hamper longer-term convergence prospects in the medium-run. The World Bank stands ready to support the structural transformation of Bulgaria. The Government is strongly committed to maintaining the currency board with the euro adoption as an exit strategy. Yet, a continued worsening in private and public sector balance sheets could trigger a loss of confidence in the currency board. As international investors take a closer look at the vulnerabilities of emerging economies, there is a large premium on strong domestic policies. While financial markets may have under-priced the risks relative to the fundamentals in Bulgaria and other countries in the region prior to the crisis, this under-pricing has now disappeared. The pendulum is now likely to swing into the opposite direction.